Ketika Obesitas Mengancam Pengelihatan: Kasus Papiledema pada Wanita Muda - Khonsa Fitri Fadilah; Rahayu Widhyasti; Tri Agus Haryono (Malahayati Nursing Journal, 2025)
ABSTRACT Papilledema is optic disc swelling caused by increased intracranial pressure (ICP) ). One of the most common causes is idiopathic intracranial hypertension (IIH), particularly affecting young obese women. This condition can threaten visual function if not promptly diagnosed and managed. To present the clinical manifestation, diagnostic workup, and management of papilledema in a patient with suspected IIH. This study used a descriptive case report design. The subject was a 25-year-old woman presenting to the ophthalmology clinic with sudden bilateral blurred vision accompanied by headache, nausea, and vomiting. Data were obtained through anamnesis, general physical examination, ophthalmologic assessments (visual acuity, funduscopy, fundus photography), and head CT scan.Examination revealed decreased visual acuity that improved with correction. Fundus photography demonstrated bilateral papilledema with optic disc edema, blurred margins, peripapillary hemorrhages, and venous congestion. Head CT showed no intracranial abnormalities. The patient, classified as overweight (BMI 28.7 kg/m²), was diagnosed with papilledema suspected to be related to IIH. Management included education on weight reduction, lifestyle modification, and supportive therapy with artificial tears and neuroprotective agents. The prognosis was favorable for life, but doubtful to poor for visual function due to the risk of permanent optic nerve damage.Papilledema in young obese women may represent a typical manifestation of IIH. Diagnosis relies on a combination of clinical features, ophthalmological findings, and imaging. Weight reduction remains the first-line therapy, while visual prognosis depends on the degree of optic nerve damage at diagnosis. Keywords: Idiopathic Intracranial Hypertension, Obesity, Papilledema, Young Women.  ABSTRAK Papiledema adalah pembengkakan kepala saraf optik akibat peningkatan tekanan intrakranial. Salah satu penyebab tersering adalah hipertensi intrakranial idiopatik, yang banyak ditemukan pada wanita muda obesitas. Kondisi ini berpotensi mengancam fungsi penglihatan bila tidak terdiagnosis dan ditangani secara tepat. Melaporkan manifestasi klinis, pemeriksaan penunjang, serta tatalaksana papiledema pada pasien dengan dugaan IIH. Penelitian menggunakan desain laporan kasus deskriptif pada seorang perempuan 25 tahun yang datang ke poliklinik mata dengan keluhan penglihatan buram mendadak bilateral, disertai sakit kepala, mual, dan muntah. Data diperoleh melalui anamnesis, pemeriksaan fisik umum, oftalmologis (visus, funduskopi, foto fundus), serta CT-Scan kepala. Pemeriksaan menunjukkan visus menurun yang membaik dengan koreksi. Foto fundus memperlihatkan papiledema bilateral dengan edema diskus optik, batas buram, perdarahan halus, dan kongesti vena retina. CT-Scan tidak menunjukkan kelainan intrakranial. Pasien didiagnosis papiledema dengan dugaan IIH pada perempuan obesitas (IMT 28,7 kg/m²). Tatalaksana meliputi edukasi manajemen berat badan, modifikasi gaya hidup, serta terapi suportif berupa tetes mata dan neuroprotektor. Prognosis kehidupan pasien baik, namun prognosis visual diragukan hingga buruk karena risiko kerusakan saraf optik permanen. Papiledema pada wanita muda obesitas merupakan manifestasi khas IIH. Diagnosis ditegakkan melalui kombinasi gejala klinis, pemeriksaan oftalmologis, dan penunjang. Penurunan berat badan tetap menjadi terapi utama, sedangkan prognosis visual bergantung pada tingkat kerusakan saraf optik saat diagnosis ditegakkan. Kata Kunci: Hipertensi Intrakranial Idiopatik, Obesitas, Papilledema, Wanita Muda